Os impactos da crise financeira de 2008 nas nações das instituições brasileiras - Lima, José Eduardo de Carvalho (2012)
The aim of this study was to investigate possible impacts from the 2008 financial crisis in the actions of the Brazilian financial institutions. Soon after two decades of instability, economic plans and unsuccessful cycles of growth inconsistent, it was finally, despite some problems, before a concrete set of opportunities to advance significantly in the financial market. Brazil is assured before the world an exceptional level of performance in the financial sector, with financial institutions that are designed as models of excellence in various segments. For this purpose, we used some descriptive statistics aggregated metrics to the various forms of risk and performance of the distributions of nominal daily net return of the stocks of companies that comprise the sector analyzed, every six months from 2005 to 2010. Was used as the benchmark Bovespa Index. Possibly due to such factors as the sharp contraction of credit, the level of distrust of investors in financial systems and reduced foreign demand for Brazilian products, made daily stock returns of individual companies, as well as the return of the index IBOVESPA market, react to the crisis with significant accumulated losses. The direction of change and shareholder value have been provided by microfundamentado framework given by the Capital Asset Pricing Model (CAPM). In the post-crisis period, the industry reacted and demonstrated a significant recovery predicted by fundamentals and stock returns of institutions exceeded the market index. While statistical analyzes were favorable to the financial sector, with lower standard deviation and good performance of the Sharpe ratios, Sortino, Treynor and Calmar. Using the CAPM, and the computational estimated regressions, testing the stock returns of financial institutions analyzed, the study demonstrated that accompanied the stock market movements, which should vary positively and devaluing the fundamentals signaled when they should, showing in accordance with the theory of asset pricing.